Capital Intensity, Firm Size, Leverage, and Tax Avoidance: Moderating Role of Audit Quality - Andriani, Feni; Halim, Kusuma Indawati (Universitas Kristen Maranatha, 2025)
Purpose − This study aims to analyze the effect of capital intensity, firm size, and leverage on tax avoidance, with audit quality as a moderating variable in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange for the period 2018-2024. Design/Methodology/Approach – The data used in this study is secondary data obtained from financial reports. The population in this study is 66 companies, and the sampling technique used is purposive sampling, so the sample in this study is 34 companies. The analysis used in this study is multiple linear regression and moderated regression analysis (MRA). Findings − The results of this study partially indicate that capital intensity, firm size, and leverage have no effect on tax avoidance. Meanwhile, audit quality weakens the positive relationship between capital intensity and tax avoidance. On the other hand, audit quality does not moderate the relationship between firm size and tax avoidance. In addition, audit quality strengthens the positive relationship between leverage and tax avoidance.Research limitations/Implications – This study has implications for policymakers and other stakeholders in ensuring that companies fulfill their tax obligations and demonstrate greater accountability. Keywords: Audit Quality, Capital Intensity, Firm Size, Leverage, Tax Avoidance